Pengaruh Inovasi Produk Dan Keberagaman Produk Terhadap Keputusan Pembelian Di Rumah Nutrisi Club Herbalife Malang - Hadista Khutsiyah Osgani; Tri Yulistyawati (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
Herbalife is a company engaged in health goods that offers a variety of health products that can meet nutritional needs to support the health of the body. Herbalife products have ingredients that can increase energy intake for the body, build muscle mass, to maintain stamina and body health. In some cases, consumers tend to compare Herbalife products with other similar nutritional products. Consumers do an alternative evaluation stage because consumers will see the price aspect of this product with the price of middle-to-upper class products. This study aims to determine the influence of product innovation and product diversity on purchasing decisions at Herbalife Malang Nutrition Club House. This study uses quantitative research involving variables of Product Innovation, Product Diversity and Purchasing Decisions.This research data was collected by distributing questionnaires to 116 respondents who were members of Club Baruna. This study used purposive sampling techniques with primary and secondary data. Data analysis in this study used descriptive analysis, validity test, reliability test, classical assumption test, multiple linear regression analysis and processed using IBM SPSS Statistic 25 for Windows. The results of data analysis conducted through hypothesis testing showed positive results where the variables of product innovation and product diversity had a positive and significant influence on purchasing decisions at the Herbalife Malang Nutrition Club House.